Molecular Magnetic Resonance Imaging Approaches Used to Aid in the Understanding of the Tissue Regeneration Marker Met In Vivo: Implications for Tissue Engineering - Towner, Rheal A. (Mary Ann Liebert, Inc., 2010)
The levels of Met, a tyrosine kinase receptor for the hepatocyte growth factor or scatter factor, are elevated during tissue regeneration, and can be used to assess tissue regeneration associated with engineered tissue grafts. This study involved the development and assessment of a novel magnetic resonance imaging (MRI) molecular probe for the in vivo detection of Met in an experimental rodent (rat) model of disease (C6 glioma). The implication of using these probes in tissue engineering is discussed. The molecular targeting agent we used in our study incorporated a magnetite-based dextran-coated nanoparticle backbone covalently bound to an anti-Met antibody. We used molecular MRI with an anti-Met probe to detect in vivo Met levels as a molecular marker for gliomas. Tumor regions were compared to normal tissue, and found to significantly (p < 0.05) decrease MR signal intensity and T(2) relaxation in tumors. Nonimmune nonspecific normal rat IgG coupled to the dextran-coated nanoparticles was used as a control. Met levels in tumor tissues were confirmed in Western blots. Based on our results, in vivo evaluation of tissue regeneration using molecular MRI is possible in tissue engineering applications.